Psoriasis-Specific RNA Isoforms Identified by RNA-Seq Analysis of 173,446 Transcripts - Kõks, Sulev; Keermann, Maris; Reimann, Ene; Prans, Ele; Abram, Kristi; Silm, Helgi; Kõks, Gea; Kingo, Kulli (Frontiers in Medicine, 2016)
Background: Several studies have been published that investigated potential links between transcriptome changes and psoriasis using microarrays and RNA-seq technologies but no previous study has analysed expression profile of alternatively spliced transcripts in psoriasis. Objectives: Identification of potential alternatively spliced RNA isoforms with disease-specific expression profile. Methods: Using our published RNA-sequencing data from psoriatic lesional (LP), psoriatic non-lesional (NLP) and normal control skin (C), we analysed the differential expression of RNA splicing variants. LP sample was compared with NLP, as was LP with C and NLP with C. Results: Transcript-based annotation analysed 173,446 transcripts (RNA isoforms) and around 9,000 transcripts were identified as differentially expressed between study groups. Several previously undescribed RNA variants were found. For instance transcript ETV3_3 (ENST00000326786) was significantly down-regulated in LP and NLP skin. ETV3 is a transcriptional repressor that contributes to the downstream anti-inflammatory effects of IL-10. We also identified diseases-specific transcripts (S100A7A, IL36RN_4 and IL36G_3) of genes already recognized to be involved in inflammation and immune response. Conclusion: Psoriasis is characterized by significant differences in the expression of RNA alternative isoforms. Description of these new isoforms improves our knowledge about this complex disease.